Blue ocean leadership - Kim, W. Chan (Harvard Business Review Press, 2014)
Managers often lack a clear understanding of what changes they could make to bring out the best in their employees. Here, the authors of the bestselling Blue Ocean Strategy offer a solution: a systematic approach to uncovering, at each level of the organization, which leadership acts and activeties will inspire employees to give their all, and a process for getting managers throughout the organization to start doing them. The gulf between the potential and the relized talent and energy of employees is vast: according to Gallup, 70% of workers are disengaged from their jobs. If companies use blue ocean leadership to conveert these workers into engaged employees, the results will be transformative.